Uncut Enamel for Optimizing Bonded Composite Restoration on Multiple Diastema Closure Cases - Kusumasari, Citra; Hayashi, Meiken; Shimada, Yasushi (UI Scholars Hub, 2022)
The main advantage of using a minimal invasive strategy concept by uncut enamel technique while doing direct composite restoration is to create a color and translucency close to the natural teeth with long-term bonding durability. Objective: This case report presents an uncut enamel technique for multiple diastema closure cases using direct composite restoration. Case Reports: an 18-year-old male and a 50-year-old female patient complained of diastema in their upper front teeth and requested aesthetic correction. Digital mock-up was made prior to the uncut enamel technique for showing the expected results to the patient and as a guidance for the clinician. Uncut enamel preparation was continued by free-hand restoration technique with a two-step self-etch adhesive system and composite resin application to correct the diastema. The teeth in the first and second cases were followed up after three months and four years, respectively. Conclusion: The uncut enamel preparation, free-hand restoration technique with two-step self-etch adhesive, and digital mock-up are viable options in the multiple diastema closure to re-create natural teeth and optimize bonding durability